The Role of Scientific Research in Modern Society - Maia GRÎU (Eastern European Journal of Regional Studies, 2016)
Research, development and innovation is for any country the engine of its economic and social development. Common concern of all countries for science and scientific research appears as a recognition of their role in ensuring the welfare of human civilization.The level of society development is determined mainly by performance of its education and research systems, educational level of its citizens, the quality of research activity products and equitable access of all potential users to the services and products of these systems.